Integrative self-sorting of coordination cages based on 'naked' metal ions. Issue 61 (29th June 2017) - Bloch, Witold M.; Clever, Guido H.
Abstract : In this review, we highlight recent approaches that facilitate integrative self-sorting of 'naked' metal ions and ligands to form multi-component, heteroleptic cage structures. Abstract : Coordination-driven self-assembly of metal ions and organic ligands has been extensively utilised over the past four decades to access a variety of nano-sized cage assemblies, with functions ranging from sensing and catalysis to drug delivery. Many of the reported examples, however, are highly symmetric architectures that contain one type of organic ligand carrying not more than a single functionality. This contrasts significantly with the level of structural and functional complexity encountered in biological macromolecular hosts, which are able to bind and chemically convert smaller molecules in their highly-decorated internal cavities. To address this disparity, rational approaches that facilitate heteroleptic assembly by regulating integrative self-sorting of metal ions and multiple ligand components have emerged. Among these, routes to access coordination cages from 'naked' metal cations that offer more than two coordination sites are still in early development, as the complexity of the self-sorted products in terms of composition and stereochemistry presents an entropic challenge. This feature article highlights recent progress in controlling integrative self-sorting of multi-component cage systems with a focus on structures composed of 'naked' metal cations and two different ligands. Once heteroleptic self-assembly strategies find a wider implementation in supramolecular design, the resultant interplay between tailored combinations of precisely positioned substituents promises enhanced functionality in nanoscale structures.